Justiça, vingança e valores humanos: um estudo sobre as motivações do julgamento criminal - Cataldo, Quésia Fernandes (2020)
The retributive justice model, used as a paradigm in Brazil, does not differentiate punishments motivated by justice or revenge due to the fine line between these two elements. Justice and revenge are considered underlying motivations of the criminal trial, implying different sentences in relation to the severity of the punishment and making it difficult for judges to act impartially. Human values are configured as an extralegal variable, that is, a personal characteristic of the judge that influences his decision, as they are elements inherent to the interpretation of social situations. Depending on the values prioritized by those who judge, the judgments in the same case can be different. In this sense, the present study aimed to evaluate the relationship between motivations of criminal judgment (justice and revenge) and human values through three studies. Study I sought to translate and adapt the Justice and Vengeance Scale (JVS) and to explore psychometric properties of validity and precision of the internal structure. The study included 143 participants aged between 19 and 75 years (M = 30, 46; SD = 6.89), the majority being female (76.9%). Study II tested confirmatory models for the factorial structure of EJV to verify evidence of validity and accuracy and included 255 participants with ages between 18 and 74 years old (M = 30.15; SD = 10.96), the majority being female (65.9%). In both, the participants answered the justice and revenge scale and the sociodemographic questionnaire, whose analyzes were carried out by SPSS version 20. Exploratory and confirmatory factor analyzes were carried out, indicating a three-factor structure for EJV, with an internal consistency index of α = xxx. Study III had 398 participants, the majority being female (67.8%) aged between 18 and 75 years old (m = 30.26; sd = 11.04), and explored the relationship between the motivations of the criminal trial of justice and revenge and human values through the analysis of networks. Participants answered the EJV, the basic values questionnaire (QVB) and the sociodemographic questionnaire. Using the R software, the qgraph package was used for network analysis and the Graphic Operator Algorithm of Lowest Shrinkage and Absolute Selection (GeLASSO). These analyzes indicated that the existence evaluative subfunction was the most central in the network; justice has correlated with this subfunction, while revenge has correlated with the normative subfunction. Despite some limitations, it is emphasized that this dissertation fulfilled its purpose and contributes to the growing body of literature on justice and revenge and its relationship with human values, important variables in this field.